Electronic and photovoltaic properties of new materials based on imidazo[1,2-a]pyrazine. Computational investigations - Zahlou, A.; Chtita, S.; Ghamali, M.; Bejjit, L.; Lakhlifi, T.; Bouachrine, Mr. (Functional Materials, 2013)
A quantum chemical investigation has been performed to explore optical and electronic properties of a series of different compounds based π-conjugated molecular materials with fused rings, on imidazo[1,2-a]pyrazines. Different electron-donor side groups as side-chain substituents were introduced in molecular backbone to investigate their effects on the electronic structure. The HOMO and LUMO energy levels as well energy gap Eg of the studied compounds have been calculated and reported. The obtained data suggest that studied molecules are good candidates for organic solar cells.